Mobile real-time surveillance of Zika virus in Brazil. Issue 1 (December 2016) - Faria, Nuno; Sabino, Ester; Nunes, Marcio; Alcantara, Luiz; Loman, Nicholas; Pybus, Oliver
Editorial summary The World Health Organization has declared Zika virus an international public health emergency. Knowledge of Zika virus genomic epidemiology is currently limited due to challenges in obtaining and processing samples for sequencing. The ZiBRA project is a United Kingdom–Brazil collaboration that aims to improve this situation using new sequencing technologies.